The LRR‐Roc‐COR module of the Chlorobium tepidum Roco protein: crystallization and X‐ray crystallographic analysis. Issue 9 (6th September 2017) - Deyaert, Egon; Kortholt, Arjan; Versées, Wim
Abstract : The Roco protein from the bacterium C. tepidum has been used as a model system to investigate the structure and mechanism of the Roco protein family. Here, the crystallization and crystallographic analysis of the LRR‐Roc‐COR construct of the C. tepidum Roco protein are reported. Abstract : Roco proteins are characterized by the presence of a Roc‐COR supradomain harbouring GTPase activity, which is often preceded by an LRR domain. The most notorious member of the Roco protein family is the Parkinson's disease‐associated LRRK2. The Roco protein from the bacterium Chlorobium tepidum has been used as a model system to investigate the structure and mechanism of this class of enzymes. Here, the crystallization and crystallographic analysis of the LRR‐Roc‐COR construct of the C. tepidum Roco protein is reported. The LRR‐Roc‐COR crystals belonged to space group P 21 21 21, with unit‐cell parameters a = 95.6, b = 129.8, c = 179.5 Å, α = β = γ = 90°, and diffracted to a resolution of 3.3 Å. Based on the calculated Matthews coefficient, Patterson map analysis and an initial molecular‐replacement analysis, one protein dimer is present in the asymmetric unit. The crystal structure of this protein will provide valuable insights into the interaction between the Roc‐COR and LRR domains within Roco proteins.